PENGARUH KOMPLEKSITAS TUGAS AUDITOR, KOMPETENSI DAN PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA PERBANKAN BUMN DI KOTA PALEMBANG) - Bela Rahmadani; Nina Sabrina; Mella Handayani; Welly Welly; Rosalina Ghazali (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the effect of the complexity of the auditor’s task, competence and experience of auditors on audit quality in BUMN banking in the city of Palembang. The type of research used is associative research. The location of the research is on BUMN banking in the city of Palembang. The data used in this study is primary data. The data collection methods used in this study were interviews and questionnaires. The data analysis technique used in this study was descriptive statistics, classical assumption tests and hypothesis testing assisted by the Statistical Program for Special Sciences (SPSS). The results of this study indicate that the complexity of the auditor’s task and competence has no effect on audit quality in BUMN banking in the city of Palembang.